Design and Development of a New Tactile Stimulator - Kazma, Coskun; Levent, Vecdi Emre; Aydin, Nizamettin (IEEE, 2019)
We have designed and implement a tactile stimulator to obtain information from the central nervous system. Our system consists of two main components. The first one is tactile stimulator, which was designed to stimulate index and middle finger tips, stimulating mechanoreceptors according to the test protocol. Second one is a personal computer running a desktop software for the implementation of test protocols. The flow is as follows; the subjects are asked the question of the test protocol through the personal computer. The parameters are then transmitted to the embedded board on the machine. The embedded board drives step motors to apply the relevant test parameters. The desktop software expects the individual to answer the question using the right or the left mouse button of the computer mouse. After answering the relevant question, the test proceeds to the next step. According to the test protocol, the stimulation process of the mechanoreceptors located at the index and middle finger tips must start and terminate at the same time. From this perspective, the embedded board with 3 18F46K22 PIC microcontrollers produces 2 square wave signals with different frequencies and amplitudes at the same time. The embedded system card developed with the PIC microcontroller is also developed with FPGA. The system has also been tested on 24 blue and white collar employees and a significant result has been obtained.
Keywords: Parallel square wave generation; Tactile Stimulator; FPGA; NEUROSENSORY ASSESSMENTS; Computer Science